Redox and metabolic reprogramming in breast cancer and cancer‐associated adipose tissue - Zakic, Tamara; Pekovic‐Vaughan, Vanja; Cvoro, Aleksandra; Korac, Aleksandra; Jankovic, Aleksandra; Korac, Bato (FEBS letters, 2024)
Redox and metabolic processes are tightly coupled in both physiological and pathological conditions. In cancer, their integration occurs at multiple levels and is characterized by synchronized reprogramming both in the tumor tissue and its specific but heterogeneous microenvironment. In breast cancer, the principal microenvironment is the cancer‐associated adipose tissue (CAAT). Understanding how the redox‐metabolic reprogramming becomes coordinated in human breast cancer is imperative both for cancer prevention and for the establishment of new therapeutic approaches. This review aims to provide an overview of the current knowledge of the redox profiles and regulation of intermediary metabolism in breast cancer while considering the tumor and CAAT of breast cancer as a unique Warburg's pseudo‐organ. As cancer is now recognized as a systemic metabolic disease, we have paid particular attention to the cell‐specific redox‐metabolic reprogramming and the roles of estrogen receptors and circadian rhythms, as well as their crosstalk in the development, growth, progression, and prognosis of breast cancer. This review focuses on deciphering the redox and metabolic profiles of breast cancer and associated adipose tissue as a part of a unique Warburg pseudo‐organ. In the light of the coupled cancer and adipose tissue redox‐metabolic reprogramming, mechanistic links to estrogen receptors, tumor microenvironment cell heterogeneity, inflammation, and circadian rhythms as important players affecting breast cancer development, progression, and prognosis are also discussed (Created with BioRender.com).